Implementasi Pendidikan Karakater di MTs Al Madinah Kecamtan Sirimau Kota Ambon - Ode, Bahtiar; Papilaya, J; Rumfot, Sumarni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Character education is a very important integral part of education in Indonesia, which can be interpreted as value education, character education, moral education, character education which aims to develop students' ability to make good decisions, maintain what is good and realize that goodness in everyday life wholeheartedly, so as to form a whole human being with character in the dimensions of heart, mind, body, taste, and spirit. The purpose of this research is to find out what character values are implemented at MTs Al Madinah, Sirimau District, Ambon City. And another goal is to find out the integration of character values in academic and non-academic activities and explore and analyze the factors that support and hinder the implementation of character education at MTs Al Madinah, Sirimau District, Ambon City. The approach used in this research is a qualitative descriptive approach. This research was conducted at MTs Al Madinah, Sirimau District, Ambon City, from February - April 2022. The subjects in this study were the head of the madrasah, the board of teachers, students and the madrasah committee. The object of this research is the implementation of character values at MTs Al Madinah, Sirimau District, Ambon City. The data collection techniques used observation, interviews, documentation and data tringulation. The results of this study indicate that MTs Al Madinah Sirimau Sub-district, Ambon City, has implemented character values such as honesty, discipline, responsibility, cooperation, respect, independence, and religion through a comprehensive approach involving academic curriculum and non-academic activities. These values are integrated in a participatory manner with strong support from the entire school community, including collaboration with external institutions. Despite challenges such as limited facilities, consistency in implementing character values at home, and limited teacher training. However, MTs Al Madinah remains committed to forming students who are noble and responsible. In accordance with the vision and mission of the madrasah which emphasizes a balance between academic achievement and character development